2014
DOI: 10.1166/jbn.2014.1940
|View full text |Cite
|
Sign up to set email alerts
|

Shape-Mediated Biological Effects of Mesoporous Silica Nanoparticles

Abstract: For biomedical applications, mesoporous silica nanoparticles (MSNs)-based theranostic agents have shown to be a promising alternative. Rational design of particulate systems should consider, beside the physicochemical properties of particle size and surface chemistry, shape features as aspect ratio (AR) and morphology. Recent advances of fabrication technologies for manufacturing different shaped MSNs and evaluation means of its in vitro and in vivo biological performance provide new aspects and wisdom in nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 297 publications
(175 reference statements)
0
30
0
Order By: Relevance
“…8 Recent work have shown that the particle shape plays a critical role in successfully realizing many of the aforementioned applications. 9 …”
mentioning
confidence: 99%
“…8 Recent work have shown that the particle shape plays a critical role in successfully realizing many of the aforementioned applications. 9 …”
mentioning
confidence: 99%
“…It should be emphasized that we are talking only about real pharmaceuticals that have official permission for medical use. The biological properties of different crystal forms of new substances, which have the prospect of becoming a drug but so far have not, have recently been studied and described rather widely [41][42][43][44][45][46][47]. As a rule, polymorphic modifications of a substance are tested, i.e., samples that differ significantly not only in habitus, but also in the molecular and crystal structure.…”
Section: Evaluation Of the Biological Propertiesmentioning
confidence: 99%
“…Among different silica formats, mesoporous silica nanomaterials are especially attractive, displaying large pore sizes, high internal volumes and surface areas (Hao et al, 2012, 2014a, 2014b, 2015; Zhou et al, 2015b). Although silica nanomaterials do not inherently possess optical or magnetic properties, these properties can be easily introduced by entrapment of fluorescent dyes or encapsulation of gold/QDs/magnetic nanoparticles, enabling the use of these materials in sensing and imaging (Slowing et al, 2007; Trewyn et al, 2007).…”
Section: Synthesis Of Glyconanomaterialsmentioning
confidence: 99%